The handbook of machine soldering SMT and TH - Woodgate, Ralph W. (John Wiley & Sons, 1996)
Sound electrical connections are the operational backbone of every piece of electronic equipment--and the key to success in electronics manufacturing. The Handbook of Machine Soldering is dedicated to excellence in the machine soldering of electrical connections. Self-contained, comprehensive, and down-to-earth, it cuts through jargon, peels away outdated notions, and presents all the information needed to select, install, and operate machine soldering equipment.